437 EFFECT OF POST-GLUCOSE CHALLENGE ON LIPID PROFILE IN PATIENTS WITH TYPE 2 DIABETES. Issue 1 (1st January 2007) - Gu, W.; Parish, R.; Huang, J.
Abstract : Purpose: Fasting samples are required for serum lipid measurement due to the concern of elevated triglycerides (TGs) from high-fat meals. Postprandial hypertriglyceridemia could also affect the low-density lipoprotein (LDL) cholesterol values routinely calculated based on the Freidewald equation. The effect of postprandial hyperglycemia mainly from carbohydrate on lipid profile is less clear, especially among diabetic patients. The purpose of this study was to determine the changes in serum lipid panel before and after a standard oral glucose loading in patients with type 2 diabetes. Methods: A convenient sample of 50 diabetic patients with fasting blood glucose < 250 mg/dL and glycated hemoglobin (HbA1c ) < 9% was recruited from a VA primary care clinic. Serum glucose and lipid profile were measured in fasting state and at 2 hours following 75 g oral glucose challenge. Paired t -test was employed for comparison of the parameters. Results: Twenty-four percent of the patients were smokers and 96% were males, with a mean age of 67 years, BMI 28.5 kg/m 2, systolic BP 130 mm Hg, and HbA1c 7.4%. Sixty-eight percent of the patients were on statin, 68% on ACE-I/ARB, and 10% on insulin. The mean values of total cholesterol (TC), LDL cholesterol, high-density lipoprotein (HDL) cholesterol, and TGs before and after glucose challenge were 166, 92, 44, 154, and 162, 92, 40, 150 (mg/dL), respectively. The decrease in TC and HDL from baseline was statistically significant ( p < .001). LDL cholesterol remained unchanged and the TG value had a nonsignificant reduction. Conclusion: In this elderly and predominantly male patient population from a VA primary care clinic, we found a significantly decreased TC and HDL levels associated with hyperglycemia from oral glucose challenge. Lipid management is one of the main treatment strategies for cardiovascular risk reduction in diabetic patients. Therefore, it is clinically important to have accurate measurement of all components of lipid profile. Although the exact mechanisms for the reduction in TC and HDL associated with postprandial hyperglycemia are unknown, a strict fasting blood sample without pretest carbohydrate intake is preferred for lipid panel analysis.